Generalised (k, t)-Narayana sequence - Singla, Roji Bala; Mishra, Vinod (Journal of the Indonesian Mathematical Society, 2024)
In this paper, we introduces Narayana sequence in two parameters, namely, (k, t)-Narayana sequence, which is generalization of classical Narayana sequence and provide some identities and matrix expressions. Further, we find relations between (k, t)-Narayana numbers and determinants and permanents of some Hessenberg matrices. We study recurrence relations and the sum of the first n terms of this sequence. We obtain some properties from matrices. Additionally, we define (k, t)−Narayana sequence for negative subscripts and derive some relations.